Stabilization of Copper Catalysts for Liquid‐Phase Reactions by Atomic Layer Deposition1. (26th November 2013) - O'Neill, Brandon J.; Jackson, David H. K.; Crisci, Anthony J.; Farberow, Carrie A.; Shi, Fengyuan; Alba‐Rubio, Ana C.; Lu, Junling; Dietrich, Paul J.; Gu, Xiangkui; Marshall, Christopher L.; Stair, Peter C.; Elam, Jeffrey W.; et al.
Abstract Atomic layer deposition (ALD) of an alumina overcoat can stabilize a base metal catalyst (e.g., copper) for liquid‐phase catalytic reactions (e.g., hydrogenation of biomass‐derived furfural in alcoholic solvents or water), thereby eliminating the deactivation of conventional catalysts by sintering and leaching. This method of catalyst stabilization alleviates the need to employ precious metals (e.g., platinum) in liquid‐phase catalytic processing. The alumina overcoat initially covers the catalyst surface completely. By using solid state NMR spectroscopy, X‐ray diffraction, and electron microscopy, it was shown that high temperature treatment opens porosity in the overcoat by forming crystallites of γ‐Al2O3. Infrared spectroscopic measurements and scanning tunneling microscopy studies of trimethylaluminum ALD on copper show that the remarkable stability imparted to the nanoparticles arises from selective armoring of under‐coordinated copper atoms on the nanoparticle surface.